(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2025)
Spent coffee ground (SCG) is a residual material considered as waste that remain after brewing coffee. Conventional brewing techniques generate large amount of SGC that are rich in lignocellulose and valuable bioactive compounds that can be exploited as functional food ingredients. SCG was used for its application in probiotic candy. This study was conducted to determine the sensory and viability of probiotic L acidophilus and L. bulgaricus in SCG chewy candy. The production process includes an SCG candy mix with potato and banana as carbohydrate source to sustain viability of probiotics. The candies produced were that with SCG, SCG-banana mix, SCG-potato mix and SCG-banana/potato mix. The SCG candy mixes were stored in refrigerated (4Â°C) and room temperature (25Â°C) until 4 weeks. All of the probiotic SCG candies met the standards on physicochemical analyses. Based on sensory evaluation, addition of carbohydrate source does not have significant differences on color, aroma, sweetness and coffee-flavor but has significant differences on chewiness, mouthfeel, overall flavor, off-flavor and overall acceptability. The best treatment is the probiotic chewy candy with banana as carbohydrate source with pH of 7.6, moisture content of 8.4%, water activity of 0.54 and TSS of 44 oBrix. The probiotic chewy candy with banana had acceptable organoleptic quality until 4 weeks of storage.